P3_10 The Extinction Criteria - McNally, Michael; Phong, Allen; Pierce, Robert; Searle, Thomas (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>This paper examines the possible early warning available before a “rogue” meteorite impact likely to cause the extinction of humanity.